Effect of Resistance Training on Hematological Blood Markers in Older Men and Women: A Pilot Study. (27th October 2009) - Bobeuf, Florian; Labonté, Mélissa; Khalil, Abdelouahed; Dionne, Isabelle J.
Abstract : The aim of this study was to examine the effects of resistance training on hematological blood markers in older individuals. Twenty-nine men and women participated to this study. Subjects were randomized in 2 groups: (1) control (n = 13 ) and (2) resistance training (n = 16 ). At baseline and after the intervention, subjects were submitted to a blood sample to determine their hematological profile (red blood cells, hemoglobin, hematocrit, platelets, leukocytes, neutrophils, lymphocytes, monocytes, mean corpuscular volume, mean corpuscular hemoglobin, mean corpuscular hemoglobin concentration, red cell distribution width). At baseline, no difference was observed between groups. Moreover, we found no significant difference after the intervention on any of these markers. A 6-month resistance program in healthy older individuals seems to have no beneficial nor deleterious effects on hematological blood parameters. However, resistance training was well tolerated and should be recommended for other health purposes. Further studies are needed to confirm these results in a large population.